Implementation of the Project Based Learning (PjBL) Learning Model Using Concrete Media to Increase the Learning Motivation of Grade IV Students - Nugraheni, Dwi Fajar (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
This study aims to increase students' learning motivation using the Project-based learning model in class IV SD Negeri 2 Glintang. This research is a Classroom Action Research conducted in two cycles. Data collection techniques were carried out by questionnaires, observation and documentation. Data analysis in this study used quantitative descriptive analysis. The results of this study indicate an increase in students' learning motivation from cycle I to cycle II. In the observation results of the first cycle, it reached the sufficient category, namely 65% and 68% for the results of the questionnaire which were in the sufficient category. In cycle II there was an increase in students' learning motivation in the good category, obtaining the average percentage of students' learning motivation scores both from observation sheets and questionnaires, namely 80% and 83%. These results indicate that the Project based learning learning model can increase student learning motivation, especially in class IV Science Science Subject at SD Negeri 2 Glintang.